Nocturnal Hypertension: Neglected Issue in Comprehensive Hypertension Management - Andi Kristanto; Randy Adiwinata; Silvia Suminto; Benny N Kurniawan; Finna Christianty; Robert Sinto (Acta Medica Indonesiana, 2016)
The body circardian rhythm affects blood pressure variability at day and night, therefore blood pressure at day and night might be different. Nocturnal hypertension is defined as increase of blood pressure >120/70mmHg at night, which is caused by disturbed circadian rhythm, and associated with higher cardiovascular and cerebrovascular events also mortality in hypertensive patients. Nocturnal hypertension and declining blood pressure pattern, can only be detected by continuous examination for 24 hours, also known as ambulatory blood pressure measurement (ABPM). Chronotherapy, has become a strategy for managing the hypertensive nocturnal patients, by taking hypertensive medication at night to obtain normal blood pressure decrease in accordance with the normal circadian rhythm and, improving blood pressure control.